John Steinbeck and Bo Beskow - Svensk Reportagetjanst:::Creator::::::::::::
John Steinbeck chats with Bo Beskow at the Bromma Airport in Stockholm before Nobel Prize Award. Beskow painted three known portraits of Steinbeck. RESTRICTED USE Original in safe